Digital Foundations Introduction to Media Design with the Adobe Creative Cloud - burrough, xtine; Mandiberg, Michael; Open Textbook Library (Open Textbook Library, 2017)
Digital Foundations uses formal exercises of the Bauhaus to teach the Adobe Creative Suite. All students of digital design and production-whether learning in a classroom or on their own-need to understand the basic principles of design in order to implement them using current software. Far too often design is left out of books that teach software for the trade and academic markets. Consequently, the design software training exercise is often a lost opportunity for visual learning. This revised edition updates the original text for use with Adobe Creative Cloud 2017 software.
Part I. Chapter 1: The Metaphor of Using Graphics Applications -- Part II. Chapter 2: Searching and Sampling - Becoming an Expert Web User -- Part III. Chapter 3: Symmetry -- Part IV. Chapter 4: Type on a Grid -- Part V. Chapter 5: Color Theory & Basic Shapes -- Part VI. Chapter 6: Line Art and Flat Graphics -- Part VII. Chapter 7: Scanning -- Part VIII. Chapter 8: Tonal Scale -- Part IX. Chapter 9: Layering and Collage -- Part X. Chapter 10: Repetition and Cloning -- Part XI. Chapter 11: Non-Destructive Editing -- Part XII. Chapter 12: Getting It Out - Digital Output for Web -- Part XIII. Chapter 13: Multiple Pages: Unity -- Part XIV. Chapter 14: Two-Page Spreads
In English.
Description based on print resource
Keywords: Communication -- Textbooks